Environmental Performance Indicators of Tunisian Companies: Analysis Via the Decision Tree - Ezzi, Ferdaws; Azouzi, Mohamed Ali; Jarboui, Anis (Asian Journal of Empirical Research, 2015)
The article at hand is an attempt to identify the various indicators that are more likely to explain the environmental performance of Tunisian companies. In this respective, the emphasis is put on diversification, innovation, intrapersonal and interpersonal skills. Indeed, they are the appropriate strategies that can designate emotional intelligence, the level of indebtedness, the firm age and size as the proper variables that support the target variable. The "decision tree", as a new data analysis method, is utilized to analyze our work. The results involve the construction of a crucial model which is used to achieve a sound environmental performance.